The Effectiveness of the Canva Application in Enhancing Students' Writing Proficiency across Learning Styles - Hafidzin, Haris Khoirul; Muzammil, Lasim; Sulistyo, Teguh (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2024)
The current research focused into the possible advantages of using Canva apps to improve writing abilities among kinesthetic, visual, and auditory learners. the objectives study of this research are: 1) To find out the effectiveness of using Canva had better achievements in writing recount texts than those taught by using picture series, 2) To find out whether learning styles affect achievement in writing by using Canva. Two classes were chosen at random to serve as the control and experimental groups. Canva was used to teach the experimental group, while non-computer-based instruction was used for the control group. To assess the efficacy of Canva use, a posttest was given following six sessions. The results indicated a significant improvement in writing achievements for students taught by using Canva compared to those without (sig. 0.000 ≤ sig. 0.05). Students that were taught using Canva had an N-Gain score of 0.52. It showed that using Canva to raise students' performance was successful, putting it in the middle range. Additionally, a factorial approach using a two-way ANOVA was employed to ascertain whether learning styles have an impact on Canva writing achievement. A significance value of 0.004 (sig. 0.004 < 0.05) was found by the computation. This led to the study’s implication that students' use of visual, auditory, and kinesthetic learning styles enhances their academic performance. The study's findings also indicate that employing media based on students' learning styles is a significant factor in improving their skills.